Modelagem matemática da secagem do feijão caupi e efeito sobre a qualidade fisiológica das sementes. - Camicia, Rafaela Greici da Motta (2013)
The cowpea bean, a culture traditionally planted in the Brazilian Northeast, has been expanding to other regions of Brazil, mostly to the Midwest, in the states of Mato Grosso and Mato Grosso do Sul, on account of its wide adaptability to tropical conditions and low production cost. Most of the seeds after harvest do not have appropriate characteristics for the storage, mainly due to high water content at harvest time. Drying is the most widely used process to preserve the quality of the product. The operation consists in removing some water contained in the fresh beans. In this context, the aim of this study was to determine and model the drying curves of cowpea beans at temperatures of 30, 40 and 50 °C, adjusting different mathematical models to experimental data, to select the one that best represents the phenomenon, determine the effective diffusion coefficient, and evaluate the physiological quality of seeds. They were seeds of cowpea bean cultivars BRS Guariba and BRS Novaera, harvested by hand, with water content of 0.21 (bs) and 0.16 (bs) respectively, dried to the level 0.11 (bs). The drying process was carried out in an experimental dryer under controlled temperatures of 30, 40 and 50 ° C and relative humidity of the drying air between 14% and 59%. The drying time for the cowpea bean seeds (BRS Guariba cultivar) was 10.4, 5.6 and 2.1 hours at temperatures of 30, 40 and 50 ° C respectively. For BRS Novaera, the drying lasted 8.7, 4.7 and 2.0 hours at temperatures of 30, 40 and 50 °C respectively. The mathematical model of Midilli was the one that best adapted to the experimental data for both cultivars. The diffusion coefficient increases with the temperature, with values from 5.047 to 12.011 x 10-11 x 10-11 m² s-1, for BRS Guariba, and from 2.482 x 10-11 to 5.187 x 10-11 m² s-1 for BRS Novaera in the temperature range from 30 to 50 °C. The relation between the effective diffusion coefficient and the drying temperature can be described by the Arrhenius equation, which has activation energy of 35.04 kJ.mol-1 and 29.76 kJ.mol-1 for liquid diffusion in the drying process of cowpea bean seeds. After the drying process, the seeds percentage of normal seedlings were more than 87%, and under the different conditions of study they presented low force, since the drying under a temperature of 40 °C was the one which produced the most satisfactory results.